A water-phase reduction-stable metal ruthenium catalyst
By reducing the sodium lignin sulfonate aqueous metal ruthenium catalyst prepared by in situ reduction of ruthenium acetate in aqueous solution, the problem of insufficient utilization of lignin resources in the prior art was solved, and diphenylmethane and o-hydroxyl dihydrogen Highly efficient catalysis in benzyl ethane hydrogenation reaction, and the catalyst cycle stability and cost are better than the prior art.
Patent Information
- Application Number
- CN202410116305.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-01-29
AI Technical Summary
In the prior art, lignin resources have not fully utilized their aromatic properties and functional group characteristics, and the methods for preparing environmentally friendly catalysts are complex and harsh, and the application of catalysts in the hydrogenation reaction of diphenylmethane and o-hydroxydiphenylmethane has not yet been achieved. See literature report.
Ruthenium acetate is prepared by using sodium lignin sulfonate in situ reduction in aqueous solution, and the catalyst is applied in the hydrogenation reaction of diphenylmethane and o-hydroxydibenzylmethane by magnetic stirring and ultrasonic. The method is used to achieve good dispersion and stability of ruthenium ions.
It realizes high yield preparation of dicyclohexylmethane and all-hydrofluorene products under mild aqueous reaction conditions. The catalyst can be recycled and has good cycle stability, and the cost is lower than that of Pt, Pd, and Rh water used in the prior art. Phase nanoparticle catalyst and significantly improve the catalytic capacity.
Smart Images

Figure CN117942987B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation and application of a water-phase reduction-stabilized metal ruthenium catalyst, specifically to an aqueous phase catalyst prepared by in-situ reduction-stabilizing ruthenium acetate with sodium lignin sulfonate in an aqueous solution, and the application of the aqueous phase catalyst in the hydrogenation reaction of diphenylmethane and o-hydroxydiphenylmethane, belonging to the technical field of preparation and application of novel environmentally friendly catalysts. Background Art
[0002] Lignin is the second most abundant biomacromolecule on earth and the main source of phenolic substances in nature. However, only about 5% of lignin resources are currently used for energy combustion such as power generation and a very small number of commercial uses, and most of them are treated as waste. In fact, people have found that lignin macromolecules with aromatic structures as skeletons and containing a large number of beneficial chemical groups can be cracked into small fragment compounds containing aromatic hydrocarbons, and also have the potential to prepare efficient catalysts through modification or functionalization.
[0003] In the existing technology, the high carbon content of lignin resources enables it to be used to prepare efficient solid acid catalysts after calcination and proper activation, and has been successfully applied in the preparation of biodiesel, hydrolysis of microcrystalline cellulose, and conversion of biomass platform compounds [Appl Catal B Environ.2016,190:103–114; Korean J Chem Eng.2017,34(1):110–117; BioResources.2018,13(2):4428–4439; Res Chem Intermed.2020,46(2):1469–1485; Int J Biol Macromol.2021,187:232–239]. Using various lignin resources as carbon material precursors, it has been found that metals can be well dispersed and loaded and stabilized by nitrogen doping and other methods to prepare efficient electrocatalysts and other redox catalysts [ACS Nano. 2016, 10 (4): 4364-4371; Environ Res Public Health. 2023, 20 (5): 4383; J Ind Eng Chem. 2024, 131: 653-661]. Although these lignin carbon-based catalysts utilize lignin resources, they completely waste the aromaticity and various functional group characteristics of the natural structure of lignin. In fact, the aromatic ring skeleton and OH, C=O, COOH, OCH in the macromolecular structure of lignin and its various derivatives are very important. 3Functional groups such as lignin have good reactivity and provide great potential for the construction and development of bio-based catalysts [Int J Biol Macromol. 2020, 155: 814–822; CN110252402A; Biomass Convers Biorefinery. 2023, 13: 12451–12465; Int J Biol Macromol. 2021, 182: 564-573; Inorg Chem Commun. 2023, 154: 110897]. However, the preparation of the above-mentioned lignin-based catalysts involves high-temperature calcination, inorganic acid modification, organic reaction modification, other raw material doping and chemical reagent reduction. The preparation process is complex, the conditions are harsh, and the environmental factors are high, and it has not yet truly reached the standard of environmentally friendly catalysts.
[0004] Some researchers have found that water-soluble derivatives of lignin or other natural polyphenols can act as both reducing agents and stabilizers in water to prepare water-dispersed and stable metal nanoparticles such as silver [Colloids Surf B Biointerfaces.2013,105:335–341; Int J Biol Macromol.2016,82:856–862], gold [Mater Lett.2015,159:451–454], platinum [ACS Omega.2020,5(15):8902–8911] and palladium [Green Chem.2012,14(4):1073; InorganicaChim Acta.2013,399:12–18; Ind Crops Prod.2023,192:116055]. The preparation methods of these nanoparticles constructed using lignin resources are clean, mild, and low-cost, eliminating the use of hazardous chemicals and petroleum-based chemicals. They can be used as chemical probes for detecting heavy metals, signal amplifiers in SERS technology, or as catalysts in certain redox template reactions. However, for actual catalytic reaction processes, different substrates and reaction directions have different requirements for the active center, chemical composition, and catalytic system of the catalyst. Although the above-mentioned nanoparticles stabilized by lignin reduction have been successfully prepared, their successful application as environmentally friendly catalysts is still very limited. In addition, due to the characteristics of different metal active centers, the requirements for suitable reducing agents, stabilizers, and related preparation conditions are quite different, and the catalytic ability and stability for different reactions are also very different. Therefore, the development of environmentally friendly catalysts for the conversion process of more biomass platform compounds is still a realistic problem that needs to be solved urgently. So far, the preparation of water-dispersed ruthenium nanoparticle catalysts using lignin derivatives and their application in the hydrogenation of diphenylmethane and o-hydroxydiphenylmethane have not been reported in the literature. Summary of the invention
[0005] The purpose of the present invention is to turn waste into treasure, using sodium lignin sulfonate, a cheap and readily available industrial byproduct, as a raw material and water as a dispersant to provide a new water-phase reduction-stable metal ruthenium catalyst and a clean preparation method thereof. The present invention also provides the efficient application of the catalyst in the hydrogenation reaction of diphenylmethane and o-hydroxydiphenylmethane.
[0006] According to the present invention, the provided sodium lignin sulfonate aqueous phase reduction stable metal ruthenium catalyst Ru@SLS aq The preparation method is as follows:
[0007] The vacuum-dried sodium lignin sulfonate was stirred with measured ultrapure water at room temperature until fully dissolved, and the concentration of sodium lignin sulfonate was 1.17-1.67×10 -3 Weigh ruthenium acetate, add it to the measured ultrapure water, ultrasonicate it until it is completely dissolved, then add it drop by drop into the sodium lignin sulfonate aqueous solution, and add ultrapure water until the concentration of sodium lignin sulfonate is 10g / L. React at 40-80℃ for 3h under magnetic stirring at 400-800rpm, then cool to room temperature, and dilute it ten times with ultrapure water to obtain a stable black opaque aqueous metal ruthenium catalyst Ru@SLS. aq .
[0008] According to the present invention, the provided sodium lignin sulfonate aqueous phase reduction stable metal ruthenium catalyst Ru@SLS aq The usage is as follows:
[0009] The substrate diphenylmethane or o-hydroxydiphenylmethane and the aqueous phase reduction-stable ruthenium catalyst Ru@SLS of sodium lignin sulfonate were added to a stainless steel autoclave at a ratio of 6 mL of aqueous phase catalyst per mmol of substrate. aq After replacing the air in the kettle with hydrogen, the reaction was carried out for 4 hours under stirring at 400 rpm, 1.5 MPa hydrogen pressure and 80°C. After the reaction was completed, the aqueous phase catalyst was recovered by static separation method, and the above steps were repeated to use it for the next cycle of catalytic reaction.
[0010] The present invention provides a sodium lignin sulfonate aqueous phase reduction stable metal ruthenium catalyst Ru@SLS aq Compared with the existing technology, it has the following characteristics:
[0011] (1)Ru@SLS aq It has excellent catalytic ability in the hydrogenation reaction of diphenylmethane and o-hydroxydiphenylmethane, and can achieve high yield preparation of dicyclohexylmethane and perhydrofluorene products under mild aqueous phase reaction conditions. The catalyst can be recycled and has good cyclic stability.
[0012] (2) Ru@SLS provided by the present inventionaq The catalyst uses metallic ruthenium as the active center. Compared with the Pt, Pd, and Rh aqueous phase nanoparticle catalysts stabilized by lignin reported in the prior art, not only is the cost greatly reduced, but the catalytic ability of the hydrogenation reaction of diphenylmethane and o-hydroxydiphenylmethane is also substantially improved.
[0013] (3) The present invention makes full use of the macromolecular polyphenol structural characteristics of sodium lignin sulfonate and the difference in the coordination ability of the anion in ruthenium acetate to achieve good dispersion and reduction of ruthenium ions in an aqueous solution under suitable conditions, as well as the encapsulation and stabilization of generated ruthenium nanoparticles, effectively controlling the dispersion and morphology of the catalytic active center, thereby presenting a mild and efficient catalytic hydrogenation ability of diphenylmethane and o-hydroxydiphenylmethane. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Attached Figure 1 The ruthenium catalyst Ru@SLS prepared in Example 5 was stabilized by aqueous reduction of sodium lignin sulfonate. aq HR-TEM and particle size distribution diagram of -5.
[0015] Attached Figure 2 The ruthenium catalyst Ru@SLS prepared in Example 5 was stabilized by aqueous reduction of sodium lignin sulfonate. aq -5's XPS spectrum.
[0016] Attached Figure 3 The ruthenium catalyst Ru@SLS prepared in Example 5 was stabilized by aqueous reduction of sodium lignin sulfonate. aq -5 Photos of the reaction system status before the catalytic reaction (a), after five cyclic catalytic diphenylmethane hydrogenation reactions (b), and after five cyclic catalytic o-hydroxydiphenylmethane hydrodeoxygenation reactions (c). DETAILED DESCRIPTION
[0017] The following examples are used to further illustrate the present invention, but are not intended to limit the present invention.
[0018] [Example 1] Ru@SLS aq -1 preparation and catalytic application
[0019] 60 mg of vacuum-dried sodium lignin sulfonate was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.07 mmol of ruthenium acetate was added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. It was added dropwise to the sodium lignin sulfonate aqueous solution. 2 mL of ultrapure water was added to the resulting mixture, and the mixture was stirred at 400 rpm at 80 ° C for 3 h, then cooled to room temperature and diluted ten times with ultrapure water to obtain a stable black opaque aqueous metal ruthenium catalyst Ru@SLS. aq -1.
[0020] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -1 and 1mmol diphenylmethane were added to a stainless steel high-pressure reactor, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0021] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -1 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel high-pressure reactor, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0022] [Example 2] Ru@SLS aq -2 preparation and catalytic application
[0023] 60 mg of vacuum-dried sodium lignin sulfonate was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.08 mmol of ruthenium acetate was added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. It was added dropwise to the sodium lignin sulfonate aqueous solution. 2 mL of ultrapure water was added to the resulting mixture. The mixture was stirred at 400 rpm at 80 ° C for 3 h, then cooled to room temperature and diluted ten times with ultrapure water to obtain a stable black opaque aqueous metal ruthenium catalyst Ru@SLS. aq -2.
[0024] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -2 and 1mmol diphenylmethane were added to a stainless steel high-pressure reactor, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0025] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -2 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel high-pressure reactor, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0026] [Example 3] Ru@SLS aq-3 preparation and catalytic application
[0027] 60 mg of vacuum-dried sodium lignin sulfonate was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.10 mmol of ruthenium acetate was added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. It was added dropwise to the sodium lignin sulfonate aqueous solution. 2 mL of ultrapure water was added to the resulting mixture. The mixture was stirred at 400 rpm at 80 ° C for 3 h, then cooled to room temperature and diluted ten times with ultrapure water to obtain a stable black opaque aqueous metal ruthenium catalyst Ru@SLS. aq -3.
[0028] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -3 and 1mmol diphenylmethane were added to a stainless steel high-pressure reactor, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0029] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -3 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel high-pressure reactor, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0030] [Example 4] Ru@SLS aq -4 preparation and catalytic application
[0031] 60 mg of vacuum-dried sodium lignin sulfonate was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.08 mmol of ruthenium acetate was added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. It was added dropwise to the sodium lignin sulfonate aqueous solution. 2 mL of ultrapure water was added to the resulting mixture. The mixture was stirred at 400 rpm and reacted at 40 ° C for 3 h. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a stable black opaque aqueous metal ruthenium catalyst Ru@SLS. aq -4.
[0032] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -4 and 1mmol diphenylmethane were added to a stainless steel high-pressure reactor, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0033] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -4 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel high-pressure reactor, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0034] [Example 5] Ru@SLS aq -5 preparation and catalytic application
[0035] 60 mg of vacuum-dried sodium lignin sulfonate was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.08 mmol of ruthenium acetate was added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. It was added dropwise to the sodium lignin sulfonate aqueous solution. 2 mL of ultrapure water was added to the resulting mixture. The mixture was stirred at 400 rpm and reacted at 60 ° C for 3 h. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a stable black opaque aqueous metal ruthenium catalyst Ru@SLS. aq -5.
[0036] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -5 and 1mmol diphenylmethane were added to a stainless steel high-pressure reactor, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0037] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -5 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel high-pressure reactor, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0038] Attached Figure 1 Ru@SLS aq The HR-TEM image of -5 shows that the ruthenium particles are well dispersed, with a particle size distribution range of 1.64-2.91nm and an average particle size of 2.34nm.
[0039] Attached Figure 2 Ru@SLSaq The XPS spectrum of -5 shows Ru at 484.21eV and 462.08eV 0 The 3p orbital characteristic peak accounts for about 89.69% of the Ru species.
[0040] Attached Figure 3 Visible Ru@SLS aq -5 has a stable black opaque appearance before the catalytic reaction. After five cycles of catalytic hydrogenation of diphenylmethane or o-hydroxydiphenylmethane, the macroscopic state of the catalyst has not changed significantly and is still in a stable black opaque state. The upper organic product and the lower aqueous catalyst have a good self-separation effect.
[0041] [Example 6] Ru@SLS aq -6 preparation and catalytic application
[0042] 60 mg of vacuum-dried sodium lignin sulfonate was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.08 mmol of ruthenium acetate was added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. It was added dropwise to the sodium lignin sulfonate aqueous solution. 2 mL of ultrapure water was added to the resulting mixture. The mixture was stirred at 600 rpm and reacted at 60 ° C for 3 h. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a stable black opaque aqueous metal ruthenium catalyst Ru@SLS. aq -6.
[0043] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -6 and 1mmol diphenylmethane were added to a stainless steel high-pressure reactor, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0044] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -6 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced 4-5 times with hydrogen, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0045] Table 1. Stable ruthenium catalyst Ru@SLS for aqueous reduction of sodium lignin sulfonate aq Catalytic hydrogenation of diphenylmethane
[0046]
[0047] Table 2. Stable ruthenium catalyst Ru@SLS for aqueous reduction of sodium lignin sulfonate aq Catalytic Hydrodeoxygenation of o-Hydroxydiphenylmethane
[0048]
[0049] [Example 7] Ru@SLS aq -7 preparation and catalytic application
[0050] 60 mg of vacuum-dried sodium lignin sulfonate was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.08 mmol of ruthenium acetate was added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. It was added dropwise to the sodium lignin sulfonate aqueous solution. 2 mL of ultrapure water was added to the resulting mixture. The mixture was stirred at 800 rpm and reacted at 60 ° C for 3 h. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a stable black opaque aqueous metal ruthenium catalyst Ru@SLS. aq -7.
[0051] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -7 and 1mmol diphenylmethane were added to a stainless steel high-pressure reactor, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0052] Take 6 mL of the sodium lignin sulfonate prepared above to reduce the stable metal ruthenium catalyst Ru@SLS in water phase aq -7 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0053] [Examples 8-11] Ru@SLS aq -5 cycle performance
[0054] The mixed system after the catalytic reaction of diphenylmethane or o-hydroxydiphenylmethane in Example 5 was allowed to stand for liquid separation to remove the upper organic phase, and the recovered aqueous catalyst was added to a stainless steel high-pressure reactor, and then 1 mmol of diphenylmethane or o-hydroxydiphenylmethane was added, and the air was replaced with hydrogen for 4-5 times, and then 1.5 MPa H 2 , stirred at 400 rpm and reacted at 80°C for 4 hours. After the reaction was completed, the mixed reaction system was taken out and allowed to stand for separation, the upper organic phase was taken for gas chromatography analysis, and the recovered aqueous phase catalyst was repeated for the above operation. The results of the four-time recycling are shown in Tables 3 and 4.
[0055] Table 3Ru@SLS aq -5 catalytic performance of diphenylmethane hydrogenation
[0056]
[0057] Table 4Ru@SLS aq Recycling performance of -5 catalyzed hydrodeoxygenation of o-hydroxydiphenylmethane
[0058]
[0059] [Comparative Example 1] Pd@SLS aq -1 preparation and catalytic performance
[0060] In a single-necked flask, 6 mL of ultrapure water, 60 mg of vacuum-dried sodium lignin sulfonate, and 0.10 mmol of sodium chloropalladate were added, and the mixture was reacted at 80 °C for 3 h under magnetic stirring at 400 rpm, cooled to room temperature, and diluted ten times with ultrapure water to obtain a sodium lignin sulfonate-stabilized aqueous Pd catalyst Pd@SLS. aq -1.
[0061] Take 6 mL of the Pd@SLS prepared above aq -1 catalyst and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 5.
[0062] Take 6 mL of the Pd@SLS prepared above aq -1 catalyst and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The mixture was stirred at 400 rpm and reacted at 80°C for 4 h. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 6.
[0063] [Comparative Example 2] Pd@SLS aq -2 preparation and catalytic performance
[0064] In a single-necked flask, 6 mL of ultrapure water, 60 mg of vacuum-dried sodium lignin sulfonate, and 0.10 mmol of potassium chloropalladate were added, and the mixture was reacted at 80 °C for 3 h under magnetic stirring at 400 rpm, cooled to room temperature, and diluted ten times with ultrapure water to obtain a sodium lignin sulfonate-stabilized aqueous Pd catalyst Pd@SLS. aq -2.
[0065] Take 6 mL of the Pd@SLS prepared aboveaq -2 catalyst and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 5.
[0066] Take 6 mL of the Pd@SLS prepared above aq -2 catalyst and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The mixture was stirred at 400 rpm and reacted at 80°C for 4 h. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 6.
[0067] [Comparative Example 3] Pd@SLS aq -3 preparation and its catalytic performance
[0068] 6 mL of ultrapure water, 60 mg of vacuum-dried sodium lignin sulfonate, and 0.10 mmol of palladium acetate were added to a single-necked flask. The mixture was reacted at 80 °C for 3 h under magnetic stirring at 400 rpm and cooled to room temperature. The mixture was diluted ten times with ultrapure water to obtain a sodium lignin sulfonate-stabilized aqueous Pd catalyst Pd@SLS. aq -3.
[0069] Take 6 mL of the Pd@SLS prepared above aq -3 catalyst and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 5.
[0070] Take 6 mL of the Pd@SLS prepared above aq -3 catalyst and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The mixture was stirred at 400 rpm and reacted at 80°C for 4 h. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 6.
[0071] [Comparative Example 4] Ag@SLS aq Preparation and catalytic performance of
[0072] 6 mL of ultrapure water, 60 mg of vacuum-dried sodium lignin sulfonate, and 0.10 mmol of silver nitrate were added to a single-necked flask. The mixture was reacted at 80 °C for 3 h under magnetic stirring at 400 rpm and cooled to room temperature. The mixture was diluted ten times with ultrapure water to obtain an aqueous phase Ag catalyst Ag@SLS stabilized by sodium lignin sulfonate.aq .
[0073] Take 6 mL of the Ag@SLS prepared above aq The catalyst and 1 mmol of diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5 MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 5.
[0074] Take 6 mL of the Ag@SLS prepared above aq The catalyst and 1 mmol of o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5 MPa H 2 The mixture was stirred at 400 rpm and reacted at 80°C for 4 h. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 6.
[0075] [Comparative Example 5] Ru@SLS aq -8 preparation and catalytic performance
[0076] 6 mL of ultrapure water, 60 mg of vacuum-dried sodium lignin sulfonate, and 0.10 mmol of hydrated ruthenium trichloride were added to a single-necked flask, and the mixture was reacted at 80 °C for 3 h under magnetic stirring at 400 rpm, cooled to room temperature, and diluted ten times with ultrapure water to obtain a sodium lignin sulfonate-stabilized aqueous Ru catalyst Ru@SLS. aq -8.
[0077] Take 6 mL of the Ru@SLS prepared above aq -8 catalyst and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 5.
[0078] Take 6 mL of the Ru@SLS prepared above aq -8 catalyst and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The mixture was stirred at 400 rpm and reacted at 80°C for 4 h. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 6.
[0079] [Comparative Example 6] Rh@SLS aq -1 preparation and catalytic performance
[0080] 6 mL of ultrapure water, 60 mg of vacuum-dried sodium lignin sulfonate, and 0.10 mmol of hydrated rhodium trichloride were added to a single-necked flask. The mixture was stirred at 400 rpm at 80 °C for 3 h and cooled to room temperature. The mixture was diluted ten times with ultrapure water to obtain a sodium lignin sulfonate-stabilized aqueous Rh catalyst Rh@SLS. aq -1.
[0081] Take 6mL of the Rh@SLS prepared above aq -1 catalyst and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 5.
[0082] Take 6mL of the Rh@SLS prepared above aq -1 catalyst and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The mixture was stirred at 400 rpm and reacted at 80°C for 4 h. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 6.
[0083] [Comparative Example 7] Rh@SLS aq -2 preparation and catalytic performance
[0084] 6 mL of ultrapure water, 60 mg of vacuum-dried sodium lignin sulfonate, and 0.10 mmol of rhodium acetate were added to a single-necked flask, and the mixture was reacted at 80 °C for 3 h under magnetic stirring at 400 rpm, cooled to room temperature, and diluted ten times with ultrapure water to obtain a sodium lignin sulfonate-stabilized aqueous Rh catalyst Rh@SLS. aq -2.
[0085] Take 6mL of the Rh@SLS prepared above aq -2 catalyst and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 5.
[0086] Take 6mL of the Rh@SLS prepared above aq -2 catalyst and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The mixture was stirred at 400 rpm and reacted at 80°C for 4 h. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 6.
[0087] [Comparative Example 8] Pt@SLS aq -1 preparation and catalytic performance
[0088] In a single-necked flask, 6 mL of ultrapure water, 60 mg of vacuum-dried sodium lignin sulfonate, and 0.10 mmol of chloroplatinic acid hexahydrate were added, and the mixture was reacted at 80 °C for 3 h under magnetic stirring at 400 rpm, cooled to room temperature, and diluted ten times with ultrapure water to obtain a sodium lignin sulfonate-stabilized aqueous Pt catalyst Pt@SLS. aq -1.
[0089] Take 6 mL of the Pt@SLS prepared above aq -1 catalyst and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 5.
[0090] Take 6 mL of the Pt@SLS prepared above aq -1 catalyst and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The mixture was stirred at 400 rpm and reacted at 80°C for 4 h. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 6.
[0091] [Comparative Example 9] Pt@SLS aq -2 preparation and catalytic performance
[0092] 6 mL of ultrapure water, 60 mg of vacuum-dried sodium lignin sulfonate, and 0.10 mmol of platinum tetrachloride were added to a single-necked flask, and the mixture was reacted at 80 °C for 3 h under magnetic stirring at 400 rpm, cooled to room temperature, and diluted ten times with ultrapure water to obtain a sodium lignin sulfonate-stabilized aqueous Pt catalyst Pt@SLS. aq -2.
[0093] Take 6 mL of the Pt@SLS prepared above aq -2 catalyst and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2 The reaction was carried out at 80°C for 4 h with stirring at 400 rpm. After the reaction was completed, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 5.
[0094] Take 6 mL of the Pt@SLS prepared above aq -2 catalyst and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then filled with 1.5MPa H 2The mixture was stirred at 400 rpm and reacted at 80°C for 4 h. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 6.
[0095] Table 5 Comparative performance of catalysts for diphenylmethane hydrogenation
[0096]
[0097] Table 6 Comparative performance of catalysts for catalytic hydrodeoxygenation of o-hydroxydiphenylmethane
[0098]
Claims
1. A water-phase reduction-stable metal ruthenium catalyst, characterized in that Ruthenium acetate is used as a metal precursor, sodium lignin sulfonate is used as a reducing agent and a stabilizer in an aqueous solution, and no other chemical reagents and organic solvents are added to directly prepare a stable aqueous phase high-efficiency catalyst; the preparation process is as follows: According to 1.17-1.67×10 per gram of sodium lignin sulfonate -3 The ruthenium acetate dissolved in ultrapure water is added dropwise into the sodium lignin sulfonate aqueous solution, and ultrapure water is added to the sodium lignin sulfonate concentration of 10g / L. The mixed solution is stirred at 400-800rpm and 40-80℃ for 3h. After cooling to room temperature, it is diluted ten times with ultrapure water to obtain a metal ruthenium catalyst stable for water phase reduction.
2. Use of the water-phase reduction-stable metal ruthenium catalyst according to claim 1 in catalyzing the hydrogenation of diphenylmethane or the hydrodeoxygenation of o-hydroxydiphenylmethane.